2009
DOI: 10.1186/1471-2334-9-195
|View full text |Cite
|
Sign up to set email alerts
|

High dose prolonged treatment with nitazoxanide is not effective for cryptosporidiosis in HIV positive Zambian children: a randomised controlled trial

Abstract: BackgroundTreatment of cryptosporidiosis in HIV infected children has proved difficult and unsatisfactory with no drugs having demonstrable efficacy in controlled trials except nitazoxanide. We hypothesised that a prolonged course of treatment with high dose nitazoxanide would be effective in treating cryptosporidiosis in HIV positive Zambian children.MethodsWe performed a double-blind, randomised, placebo controlled trial in paediatric patients in the UTH in Lusaka. The study included HIV positive children be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
150
3
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(156 citation statements)
references
References 17 publications
1
150
3
2
Order By: Relevance
“…Likewise, nitazoxanide, which is the only FDA-approved drug for the treatment of cryptosporidiosis in immunocompetent patients older than 1 year (16), is not approved for HIV-infected patients (17). Also, clinical trials demonstrated that there were no differences in mortality or parasitological responses between the patients who received nitazoxanide and placebo (18)(19)(20). New drugs are clearly needed.…”
mentioning
confidence: 99%
“…Likewise, nitazoxanide, which is the only FDA-approved drug for the treatment of cryptosporidiosis in immunocompetent patients older than 1 year (16), is not approved for HIV-infected patients (17). Also, clinical trials demonstrated that there were no differences in mortality or parasitological responses between the patients who received nitazoxanide and placebo (18)(19)(20). New drugs are clearly needed.…”
mentioning
confidence: 99%
“…In malnourished children, a survival advantage was shown with nitazoxanide treatment, but the response rate was poor [7,8]. Furthermore, randomized trials show no benefit with nitazoxanide treatment in patients with AIDS [8,17]. More-effective parasite-specific drugs are clearly needed for treating cryptosporidiosis.…”
mentioning
confidence: 99%
“…Further, the mechanism of action of nitazoxanide against Cryptosporidium is unknown, and it is speculated that it may act via a nonspecific immunomodulatory effect [7,16]. In malnourished children, a survival advantage was shown with nitazoxanide treatment, but the response rate was poor [7,8]. Furthermore, randomized trials show no benefit with nitazoxanide treatment in patients with AIDS [8,17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the only available drug for human infections (nitazoxanide -Romark Laboratories, Florida, USA), has variable efficacy (Abubakar et al, 2007;Amadi et al, 2009) and an effective vaccine has yet to be developed (Mead, 2014;Ryan et al, 2016). Halofuginone lactate (Halocur; Intervet, New Zealand) is commercially available against cryptosporidiosis in dairy calves, with variable efficacy (Trotz-Williams et al, 2011;Almawly et al, 2013).…”
Section: Introductionmentioning
confidence: 99%